Study on the Data Management Platform of Liangshan Tourism - M. Zhang (Journal of Information & Systems Management, 2017)
With the development of computer systems, the project of poverty alleviation in rural areas has also started to step into scientific standardization. How to implement an effective poverty reduction plan according to the computer science is a work that needs to be carried out in line with China’s national conditions. In this paper, the Liangshan area of China through tourism to the case of poverty alleviation as the background. Introduces the overview of the thoughts on poverty alleviation in large data management platform. Make use of computer network system application under the poverty alleviation and development documentation riser information acquisition system, making the poverty alleviation work in information work reflects the thousands of the effect, the poverty alleviation work standardization, standardization and efficiency has been remarkable effect. Practice has proved that the use of computer network system to sort out the poverty relief materials, can make the work more effective, is a practical tool and means.